Fiscal policy in the 1920s and 1930s: How much different it is from the post war period's policies? - Matti Virén (Bank of Finland, 2005)
This paper deals with the fiscal behaviour of governments in the 1920s and 1930s.The intention is to see whether there were the same features in government behaviour as in the post-World War II era.In particular, attention is paid to asymmetric fiscal policies, ie the question of whether government deficits react differently to income growth and inflation during depressions and booms.The analysis is carried out using data primarily from the League of Nations.The data come from 32 countries and covers the period 1925-1938.Estimation results suggest the in pre-war period deficits were much less sensitive to output and did not show as many asymmetric features as in post-war period.Otherwise, the same regularities apply to the empirical results.In particular, this is true with the disciplinary role of government debt in terms of budget deficits.
URN:NBN:fi:bof-20140807319
Keywords: E62; H62; 330; fiscal policy; deficit; asymmetric behaviour